Cutting of Soils - Zelenin,A. N. (1964)
The large-scale earthwork performed annually in the Soviet Union not only calls for a complete mechanization of the operations involved but for continuing them under winter conditions at a high efficiency and with the least power expenditure. The excavation of frozen soils has been a laborious operation, its cost many times higher than the cost of analogous operations performed in summer. Almost all the types of excavating machinery are little used during the winter because of the high strength of frozen soils. The existing methods of excavating frozen soils are given and discussed. (Author) Trans. from mono. Rezanie Gruntov, Moscow, 1959.